The Impact of Social Media Marketing on Purchase Decision: Exploring the Moderating Role of Brand Awareness among Instagram Users - Amelia Pulukadang (Applied Quantitative Analysis, 2025)
The rapid development of digital technology has significantly transformed consumer behavior in accessing information and making purchasing decisions. Among various platforms, Instagram has emerged as a dominant medium where social media marketing (SMM) strategies are widely employed to reach and influence consumers. However, the effectiveness of SMM is not always straightforward, as its impact on purchase decisions can be strengthened or weakened by other factors, particularly brand awareness. Consumers tend to favor brands they recognize, making brand awareness a critical element in the decision-making process. This study investigates the influence of SMM on purchase decisions with brand awareness as a moderating variable. The population consisted of 1,196 customers of Teman Publikasi – Research Synergy Institute (RSI) within the period of November 2024 to April 2025. Using Krejcie and Morgan’s sampling table, 64 respondents were selected and surveyed with a Likert scale questionnaire. Data were analyzed through multiple linear regression and moderated regression analysis (MRA) to assess both direct and moderating effects. The findings reveal that the five SMM dimensions; entertainment, interaction, trendiness, customization, and word of mouth positively and significantly influence purchase decisions. Furthermore, brand awareness significantly moderates this relationship but in a negative direction, suggesting that higher consumer brand awareness tends to reduce the effectiveness of SMM strategies. This research contributes to the literature by offering empirical evidence on the dual role of brand awareness in digital marketing effectiveness. For practitioners, the study highlights the importance of designing SMM strategies that align with consumer familiarity to avoid diminishing returns.